Transparent, Anisotropic Biofilm with Aligned Bacterial Cellulose Nanofibers. (23rd February 2018) - Wang, Sha; Li, Tian; Chen, Chaoji; Kong, Weiqing; Zhu, Shuze; Dai, Jiaqi; Diaz, Alfredo J.; Hitz, Emily; Solares, Santiago D.; Li, Teng; Hu, Liangbing
Abstract: Cellulose nanofibrils are attractive as building blocks for advanced photonic, optoelectronic, microfluidic, and bio‐based devices ranging from transistors and solar cells to fluidic and biocompatible injectable devices. For the first time, an ultrastrong and ultratough cellulose film, which is composed of densely packed bacterial cellulose (BC) nanofibrils with hierarchical fibril alignments, is successfully demonstrated. The molecular level alignment stems from the intrinsic parallel orientation of crystalline cellulose molecules produced by Acetobacter xylinum. These aligned long‐chain cellulose molecules form subfibrils with a diameter of 2–4 nm, which are further aligned to form nanofibril bundles. The BC film yields a record‐high tensile strength (≈1.0 GPa) and toughness (≈25 MJ m −3 ). Being ultrastrong and ultratough, yet the BC film is also highly flexible and can be folded into desirable shapes. The BC film exhibits a controllable manner of alignment and is highly transparent with modulated optical properties, paving the way to enabling new functionalities in mechanical, electrical, fluidic, photonics, and biocompatible applications. Abstract : A transparent and anisotropic cellulose biofilm from bacteria cellulose (BC) is constructed via a well‐developed stretching process. The hierarchical alignment of high quality cellulose fibrils renders the biofilm ultrastrong and ultratough. With tailored nanoscale and microscale morphology of stretched BC paper, the optical properties can be dramatically modulated with well‐controlled anisotropic transmission patterns, enabling new photonic applications.